A Review and Evaluation of Recent Scholarship on America’s War in Vietnam - Jervis, David (New Dynamics in Asia, 2020)
This review examines three recently-published books about the Vietnam War: Max Hastings, Vietnam: An Epic Tragedy, 1945-1975, Max Boot, The Road Not Taken: Edward Lansdale and the American Tragedy in Vietnam, and Brian VanDeMark, Road to Disaster: A New History of America’s Descent into Vietnam. As indicated by the books’ titles, they all depict the war as a “tragedy,” “a disaster,” etc. The review will detail their explanations for the Vietnam tragedy and evaluate the alternatives they suggest.